Brain injuries can set up an epileptogenic neuronal network. (October 2021) - Pototskiy, Esther; Dellinger, Joshua Ryan; Bumgarner, Stuart; Patel, Jay; Sherrerd-Smith, William; Musto, Alberto E.
Highlights: Hyperexcitable state as an early manifestation of epilepsy. Kindling as mechanism for seizure development present in specific brain areas. Use of oscillatory studies in psychiatric disorders that are comorbid with epilepsy. Relevance of the type of brain injury to seizure type and frequency. Abstract: Development of epilepsy or epileptogenesis promotes recurrent seizures. As of today, there are no effective prophylactic therapies to prevent the onset of epilepsy. Contributing to this deficiency of preventive therapy is the lack of clarity in fundamental neurobiological mechanisms underlying epileptogenesis and lack of reliable biomarkers to identify patients at risk for developing epilepsy. This limits the development of prophylactic therapies in epilepsy. Here, neural network dysfunctions reflected by oscillopathies and microepileptiform activities, including neuronal hyperexcitability and hypersynchrony, drawn from both clinical and experimental epilepsy models, have been reviewed. This review suggests that epileptogenesis reflects a progressive and dynamic dysfunction of specific neuronal networks which recruit further interconnected groups of neurons, with this resultant pathological network mediating seizure occurrence, recurrence, and progression. In the future, combining spatial and temporal resolution of neuronal non-invasive recordings from patients at risk of developing epilepsy, together with analytics and computational tools, may contribute to determining whether the brain is undergoing epileptogenesis in asymptomatic patients following brain injury.